# SBP-Program

## Subtracting monomials with exponents

How to subtract monomials with exponents? How to subtract monomials with exponents of one?

### Examples of subtracting monomials with exponents

Example of subtracting monomials with exponents.

Subtract the following monomials with exponents

64t6 - 60t6

Solution.

64t6 - 60t6 =
4t6

Example of subtracting monomials with exponents.

Subtract the following monomials with exponents

7s7 - s7

Solution.

7s7 - s7 =
7s7 - 1 * s7 = 6s7

Example of subtracting monomials with exponents.

Subtract the following monomials with exponents

65u - 64u

Solution.

Where are the exponents here? The exponent is equal to one.

65u - 64u =
65u1 - 64u1 =
u1 = u

Example of subtracting monomials with exponents.

Subtract the following monomials with exponents

54v5 - 50v5 - 4w5

Solution.

Here 54v5 and 50v5 are like terms (monomials). We can subtract them

54v5 - 50v5 = 4v5

The 4v5 and 4w5 are unlike terms (monomials). We cannot subtract them.

54v5 - 50v5 - 4w5 =
4v5 - 4w5